Assessment of drinking water quality of household bore well plants and WASA water supply system: A case study of Allama Iqbal Town Lahore: Assessment of drinking water quality - Ashraf, Mahmoona; Ahmed, Ifthikhar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
The current study has been completed by collecting the 20 water samples from Allama Iqbal Town Lahore, including ten from WASA (Water And Sanitation Agency) filter plants in Iqbal Town other samples were collected from different depths from Allama Iqbal Town Lahore. After the collection of water samples, these were taken to the green lab for physiochemical analysis of samples. Water samples were subjected to Physicochemical analysis that includes temperature, pH, Total Dissolved Solids, Total Hardness, Chloride, Arsenic, Cadmium, Sodium, Nickle, Fluoride. APHA techniques were used to analysis of water samples. Comparison of samples results with values given by the World Health Organization, represented by graphs and location maps. The Filtration plant and tap water samples were odourless, tasteless, and colourless. The amount of Lead in all the parameters was below the detectable level. Correlation analysis was applied to all the parameters to check out the deep relationship among all the parameters.The correlation results showed that with the increase of pH value, all studied traits values were increased except turbidity Physiochemical parameters in all water samples of WASA (Water And Sanitation Agency) filtration plants were within the permissible limits. It revealed that water samples of filtration plants were fit for drinking purposes. Physiochemical parameters in all water samples collected from the different depths of Lahore were not within the permissible limits, and it revealed that the tap water had arsenic amount and water collected from shallow depth have not permissible limit of sulphate, Total Hardness and Total Dissolved Solids. This showed that Tap water samples were unfit for drinking.